2022
DOI: 10.3390/ph15060685
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Tetrazine Ligation Tools for Pretargeted Nuclear Imaging

Abstract: Tetrazine ligation has gained interest as a bio-orthogonal chemistry tool within the last decade. In nuclear medicine, tetrazine ligation is currently being explored for pretargeted approaches, which have the potential to revolutionize state-of-the-art theranostic strategies. Pretargeting has been shown to increase target-to-background ratios for radiopharmaceuticals based on nanomedicines, especially within early timeframes. This allows the use of radionuclides with short half-lives which are more suited for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 133 publications
0
23
0
Order By: Relevance
“…The above highlighted the poor stability of the tetrazine core under typical S N 2 nucleophilic substitution conditions with [ 18 F]fluoride, that is, prolonged heating under basic conditions, and thus represents the biggest challenge in radiolabelling tetrazines 19,32,46 . More recently, Bratteby et al 46 have reported a method for the radiolabelling of base sensitive tetrazines using polyanionic preconditioning agents for the quaternary ammonium ion exchange cartridges used for [ 18 F]fluoride trapping and weak bases as [ 18 F]fluoride eluents.…”
Section: Brain Penetrant Tcosmentioning
confidence: 99%
See 4 more Smart Citations
“…The above highlighted the poor stability of the tetrazine core under typical S N 2 nucleophilic substitution conditions with [ 18 F]fluoride, that is, prolonged heating under basic conditions, and thus represents the biggest challenge in radiolabelling tetrazines 19,32,46 . More recently, Bratteby et al 46 have reported a method for the radiolabelling of base sensitive tetrazines using polyanionic preconditioning agents for the quaternary ammonium ion exchange cartridges used for [ 18 F]fluoride trapping and weak bases as [ 18 F]fluoride eluents.…”
Section: Brain Penetrant Tcosmentioning
confidence: 99%
“…PET imaging of pathology in the brain has largely relied on the use of small lipid soluble ligands, which passively diffuse across the BBB or polar molecules that mimic endogenous molecules and exploit active transport systems to cross the BBB. Pretargeting has the potential to greatly expand the scope of PET imaging agents available for interrogation of diseases that affect the brain, and as described above, this has largely focussed on the IEDAA reaction between activated tetrazines and TCOs 2,19,58 . Pretargeting efforts in the oncology space are now reaching clinical trial stage in humans 59,60 ; however, we are still waiting to see similar successes with pretargeting in the brain.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 3 more Smart Citations